MICROCREDIT AUX PETITS PRODUCTEURS AGRICOLES : Initiatives et défis dans la région de Boga en Ituri, RD Congo - Salumu, Fiston WANDJA; Blaise, MUGUSU KATAKA; BAISOMBI BWANYE Eugène (IJRDO - Journal of Business Management, 2020)
Now more than ever in the world, the problem of poverty is in the center of the preoccupations of the individuals like societies. To pass a vicious circle to a virtuous circle, we must attack poverty in order to institute a strong growth that, on his/her/its turn will permit to reduce poverty. In the context of the African agriculture, the income generated by the merchandising of the surplus is affected to the satisfaction many needs of the household, to such sign that the liquid capital destined to the saving or the accumulation appears like derisory and distinctly insufficient to cover the possible loads of exploitation. More serious again, it is the fact that it often arrives that in period of seedling, the completely resourceless household either incapable to get a stock in seeds in sufficient quantity. Veils the aspect of the problematic of the financing of agriculture, while knowing that financing can be solicited for other loads of exploitation as: other inputs, remuneration for the hand-d’œuvre, investment (construction, acquirement fundamental capital). The present text has for objective to analyze the problematic of the farming credit in the region of Boga in Ituri, that is to say financing by the agriculturists of the production, in other words of the liquid capital of which they have need to buy the inputs necessary to the improvement of the productivity and to the growth of the volume of the production. It will be therefore essentially question of the agricultural credit.